2020
DOI: 10.1021/acsomega.9b03522
|View full text |Cite
|
Sign up to set email alerts
|

EHBP1 SNPs, Their Haplotypes, and Gene–Environment Interactive Effects on Serum Lipid Levels

Abstract: The associations between single nucleotide polymorphisms (SNPs) rs2710642 and rs10496099 and their effect on the EH domain-binding protein 1 (EHBP1) gene and serum lipid profiles remain uncertain. This study was performed to investigate the two EHBP1 SNPs in Han and Maonan populations, including their association, haplotypes, and effects on serum lipid levels. Two EHBP1 SNPs in 564 Han and 796 Maonan participants were genotyped by high-throughput sequencing, and then the genotype and haplotype distributions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The rs2710642G-rs10496099T-rs3132584G-rs3130685C-rs2222896G-rs2278075A and rs2710642G-rs10496099T-rs3132584G-rs3130685T-rs2222896G-rs2278075A interactions were associated with reduced and increased IS risk, respectively. Many studies have identified that haplotypes have a more significant impact on phenotype than a single SNP ( Liu et al, 2020 ), and the association between haplotypes and phenotypes is more helpful for understanding local ancestral genome information and population genetic structure ( Locke et al, 2015 ). There was strong LD ( D ' > 0.8 or R 2 > 0.5) between the EHBP1 rs2710642 and rs10496099 SNPs in the three groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rs2710642G-rs10496099T-rs3132584G-rs3130685C-rs2222896G-rs2278075A and rs2710642G-rs10496099T-rs3132584G-rs3130685T-rs2222896G-rs2278075A interactions were associated with reduced and increased IS risk, respectively. Many studies have identified that haplotypes have a more significant impact on phenotype than a single SNP ( Liu et al, 2020 ), and the association between haplotypes and phenotypes is more helpful for understanding local ancestral genome information and population genetic structure ( Locke et al, 2015 ). There was strong LD ( D ' > 0.8 or R 2 > 0.5) between the EHBP1 rs2710642 and rs10496099 SNPs in the three groups.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the WWOX rs2278075 SNP was associated with CVD ( p = 5.0 × 10 −9 ) ( Joseph et al, 2017 ). In a previous study in Guangxi Maonan population, we revealed that the EHBP1 rs2710642 and rs10496099, TUBB rs3132584 and rs3130685, and WWOX rs2222896 SNPs interacted with several environmental factors to modify blood lipid profiles ( Kathiresan et al, 2007 ; Liu et al, 2020 ). However, the association between these genes and the risk of CAD or IS in Chinese populations is unclear.…”
Section: Introductionmentioning
confidence: 92%
“…The participants were aged 18–90 years with an average age of 56.6 ± 13.1 years in controls and 56.7 ± 12.3 years in hypertensives. The detailed description of the selection criteria for Maonan participants can be found in two previous studies ( 24 , 30 ). Besides, all participants were also demonstrated to be Maonan ethnic group by Y chromosome and mitochondrial diversity studies ( 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several independent GWAS have revealed that SNPs in EHBP1 are associated with cholesterol metabolism. 25,27,33 Given that the liver is the main organ involved in cholesterol metabolism and excessive hepatic cholesterol accelerates fibrotic NASH progression, we analyzed the EHBP1 expression profile in liver cells. We interrogated a publicly available scRNA-seq dataset that examined liver cells isolated from human healthy livers versus cirrhotic livers with extensive fibrosis.…”
Section: Ehbp1 Expression Is Reduced In Human and Mouse Fibrotic Nash...mentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have revealed that several single nucleotide polymorphisms (SNPs) in EHBP1, the gene that encodes EH domain binding protein 1 (EHBP1), are associated with cholesterol. [25][26][27][28] For instance, the intronic EHBP1 SNP rs10496099 T>C variant is associated with decreased serum LDL and total cholesterol in a cohort of patients with coronary artery disease, 28 though the mechanisms underlying this association and the role of EHBP1 in hepatic cholesterol metabolism are unknown. EHBP1 was originally identified as an interaction partner of the Eps15-homology domain-containing protein (EHD) family, which comprises four members (EHD1-4) essential for endocytic membrane trafficking.…”
Section: Introductionmentioning
confidence: 99%